Strategi Inovatif dalam Menghadapi Degradasi Ekosistem: Kajian Terbaru Tentang Peran Vital Hutan Mangrove dalam Konservasi Lingkungan - Asokhiwa Zega; Nelvia Mai Susanti; Rahmat Tillah; Destriman Laoli; Betzy Victor Telaumbanua; Ratna Dewi Zebua; Januari Dawolo; Okniel Zebua; Angel Sri Ayu Gea (Asosiasi Riset Ilmu Tanaman dan Hewan Indonesia, 2024)
The purpose of this study is to investigate the impact of degradation on mangrove forest ecosystems and analyze innovative strategies used to maintain the sustainability of these ecosystems. The method used is the literature review method, in which various sources of relevant scientific literature are systematically evaluated. The results of this study show that mangrove forest degradation has serious consequences for coastal ecosystems, including biodiversity loss, increased risk of natural disasters, and decreased water quality. However, various strategies have been developed to address these challenges, including ecosystem restoration, sustainable management, local community participation, and the application of modern technology. A thorough discussion of the findings reveals that the integration of these strategies can provide effective solutions in preserving mangrove forests and strengthening the resilience of coastal ecosystems. The practical implication of this study is the importance of adopting innovative strategies in environmental management, while future research directions include increasing collaboration among stakeholders and developing more advanced technologies to support sustainable mangrove forest conservation.